Investigating the Impact of Leadership Styles and Feedback Behavior on Employee Creativity Growth with the Mediating Role of Communication Mechanism (in Public Clinics of Zanjan City) - Reza Pirayesh; Hamed Rastegarnia; Fatemeh Alilou (Tehran University of Medical Sciences, 2023)
Background and Objective: Employee creativity is a key element for achieving sustainable competitive advantage in both private and public organizations. This study aims to explore the influence of leadership styles and feedback behavior on employee creativity growth, considering the mediating role of the communication mechanism among employees of public clinics in Zanjan. Materials and Methods: This applied study follows a descriptive-survey approach. Data were collected through field observations, questionnaire distribution, and library research related to the study variables. The statistical population included all employees of public clinics in Zanjan. From 209 people, 135 were randomly selected as the sample based on Cochran's formula. The questionnaires were distributed and completed by these individuals. Data collected via questionnaires were analyzed using structural equation modeling with PLS and SPSS software. Results: Feedback behavior (coefficient = 0.256), leadership styles (coefficient = 0.543), and the communication mechanism (coefficient = 0.126) significantly influenced employee creativity. Additionally, feedback behavior (coefficient = 0.267) and leadership styles (coefficient = 0.348) significantly impacted the communication mechanism. The results also indicated that the communication mechanism effectively mediated the relationship between leadership styles (coefficient = 0.044) and feedback behavior (coefficient = 0.034) on employee creativity growth. Conclusion: The findings suggest that leadership styles and feedback behavior significantly influence employee creativity growth through the mediating role of the communication mechanism. Organizational managers should leverage these factors to enhance their employees' creativity